Proposed new design scheme of Volkswagen Center for Auto Dunia Sdn Bhd Lot 137, Jalan Sultan Ismail, Kuala Lumpur / Noor Arzieana Ismail - Ismail, Noor Arzieana (Faculty of Architecture, Planning and Surveying, 2006)
The objectives of this project are to form a center for Volkswagen as a part of its oneroof marketing vehicle in Malaysia and to develop a design scheme that would express its corporate identity which is well-established as one of dominant automotive company. This project offers a comprehensive range of facilities and professional services which are rendered according to the guideline set-up by the client’s. A series of interview and observation had been conducted in collecting relevant data and information. A set of sample (questionnaires) had been distributed to various group such as public, Volkswagen car owners and automotive - link companies. The finding of this research shown that it needs to be commercialized and to cater for the public as well as the Volkswagen lovers. It also gives an advantage to clients to expose the new Volkswagen product to the customers. To achieve a high quality of Volkswagen Center, we specified the design according to the guideline of Volkswagen Dealership Asia-Pacific. Share the experience most incredible Volkswagen Center that perhaps one day will be one of the best selling car in Malaysia.